Matrix multiplication with a hypercube algorithm on multi-core processor cluster (2015)
The algorithm of multiplication of matrices of Dekel, Nassimi and Sahani or Hypercube is analysed, modified and implemented on multicore processor cluster, where the number of processors used is less than that required by the algorithm n33. 23, 43 and 83 processing units are used to multiply matrices of the order of 10x10, 102x102 and 103X103. The results of the mathematical model of the modified algorithm and those obtained from the computational experiments show that it is possible to reach acceptable speedup and parallel efficiencies, based on the number of used processor units. It also shows that the influence of the external communication link among the nodes is reduced if a combination of the available communication channels among the cores in a multi-core cluster is used.